Christian Koch, Daniel Reimann (eds.) As Variedades do Português no Ensino do Português Língua Não Materna. Tübingen: Narr Francke Attempto, 2019, 225 pp. ISBN 978-3-8233-8221-8 - Manole, Veronica (Linguarum Arena, 2020)
.